Nodal β spectrins are required to maintain Na+ channel clustering and axon integrity - Cheng-Hsin Liu; Sharon R Stevens; Lindsay H Teliska; Michael Stankewich; Peter J Mohler; Thomas J Hund; Matthew N Rasband (eLife, 2020)
Clustered ion channels at nodes of Ranvier are critical for fast action potential propagation in myelinated axons. Axon-glia interactions converge on ankyrin and spectrin cytoskeletal proteins to cluster nodal Na+ channels during development. However, how nodal ion channel clusters are maintained is poorly understood. Here, we generated mice lacking nodal spectrins in peripheral sensory neurons to uncouple their nodal functions from their axon initial segment functions. We demonstrate a hierarchy of nodal spectrins, where β4 spectrin is the primary spectrin and β1 spectrin can substitute; each is sufficient for proper node organization. Remarkably, mice lacking nodal β spectrins have normal nodal Na+ channel clustering during development, but progressively lose Na+ channels with increasing age. Loss of nodal spectrins is accompanied by an axon injury response and axon deformation. Thus, nodal spectrins are required to maintain nodal Na+ channel clusters and the structural integrity of axons.